Chemical reaction between polymers (PC, PMMA, and PET) and oxygen gas during Ar+ irradiation - Park, Sung-Chul; Jung, Hyung-Jin; Koh, Seok-Keun (Materials Research Society Symposium - Proceedings, 1995)
A surface of PC, PMMA, and PET samples irradiated with Ar+ ion of 1 keV energy with and without oxygen environment was investigated by contact angle measurement and x-ray photoelectron spectroscopy (XPS) spectra. Contact angle of water droplets on the irradiated surface of the polymers decreased and remained almost constant with increasing Ar+ irradiation without oxygen. However, when the polymers were irradiated under oxygen environment, the contact angle markedly decreased with increasing ion dose up to 1016 ions/cm2. XPS results show that, after Ar+ irradiation under oxygen, hydrophilic groups were developed on PC, PMMA, and PET. The peak ratio (O/C) of PET irradiated without oxygen decreased with increasing ion dose, whereas that of PET irradiated under oxygen increased with ion dose up to 1016 ions/cm2.